Between Blocs And Blockades: Qatar’s Diplomatic Dilemma And Strategic Maneuvers - Sargsyan, Knarik (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The article aims to analyze the dynamics of the 2017 Qatar diplomatic crisis in the context of the transforming geopolitics of the Gulf. The goal of the article is to examine the political causes of the crisis, which are directly related to regional competition and the change of power balance in the Gulf region, and to reveal why Qatar's diplomatic crisis was resolved years later without any concessions from Qatar. The article focuses on Qatar's foreign policy ambitions, Saudi Arabia's harsh opposition against it, and Doha's further expansion, which ultimately led to Qatar's five-year blockade. The study also examines the resolution of the crisis and the normalization of the relations between Saudi Arabia and its allies with Qatar, which was conditioned by the imperative to stabilize the security environment in the region. Saudi Arabia wanted to demonstrate that Riyad will continue to be the most influential player in the Gulf region. Qatar did not make tangible concessions but accepted the rules of the game
Keywords: Security complex